Surface composition of PdCuAu ternary alloys: a combined LEIS and XPS study. (20th May 2015) - Tarditi, Ana M.; Imhoff, Carolina; Miller, James B.; Cornaglia, Laura
<x xml:space="preserve">Abstract</x> PdCuAu ternary alloy samples with different composition were synthesized on top of ZrO2‐modified porous stainless steel disks by the sequential electroless deposition technique. The structure, morphology and bulk composition of the samples were characterized by X‐ray diffraction (XRD), scanning electron microscopy and energy dispersive X‐ray spectroscopy (EDX). Complete alloy formation with a pure fcc phase for the Pd71Cu26Au3, Pd70Cu25Au5 and Pd67Cu24Au9 samples and a bcc structure for the Pd62Cu36Au2 and Pd60Cu37Au3 samples were obtained upon annealing at 500 °C for 120 h as revealed by XRD. A combination of low‐energy ion scattering (LEIS) and X‐ray photoelectron spectroscopy (XPS) was used to investigate the surface properties of the PdCuAu alloys. XPS results confirmed alloy formation under the annealing conditions. XPS analysis also revealed that the near‐surface regions of the alloys became enriched in Pd with respect to the bulk composition determined by EDX. In contrast, LEIS and angle‐resolved XPS analyses showed that the top‐most surface layers in all samples were copper‐rich compared with the bulk composition. This high Cu surface concentration could impart resistance to bulk sulfide formation to the PdCuAu alloy membranes. Copyright © 2015 John Wiley & Sons, Ltd.